Production technology for entomopathogenic fungus using a biphasic culture system - Machado, Ana Carolina Ribeiro; Monteiro, Antonio Carlos; de Almeida, Aline Maria Belasco; Geraldo Martins, Maria Inez Espagnoli (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this research was to evaluate combinations of liquid media obtained from agro-industrial residues and by-products, with solid media prepared with mixtures of grains and their derivatives, aiming to increase the production of JAB 02 and JAB 45 isolates of Lecanicillium lecanii. Sporulation, conidial viability and process yield were evaluated as well as the production costs using the JAB 45 isolate as a model system were analyzed. The production of JAB 02 was not increased using the biphasic culture. For JAB 45, some combinations provided an increase in yield, especially cheese whey with wheat bran and wheat grain, with lower production costs. Viability was not influenced by the production method, and the combinations showed no differences in the process yield. The biphasic method is suitable for the production of L. lecanii, and proves to be an appropriate technology to use in mass production by biofactories.